55.6k views
2 votes
Solve the formula for the indicated variable. k=g-d/c for g

User Ikary
by
5.9k points

2 Answers

3 votes

k=g-d/c for g


Switch sides to get g on left side


G-d/c= k


Add d/c both sides to get g alone


G= d/c+k


User TheBW
by
5.7k points
1 vote
Just like any other variable, we complete the same process


k = g - (d)/(c) \\ k + (d)/(c) = g \\ (kc + d)/(c) = g \\
Now we can test it, let's say k=4, d=6, and c=2, let's find the value of g

4 = g - (6)/(2) \\ 4 + 3 = g \\ 7= g

OR


(kc + d)/(c) = g \\ \\ ((4 * 2) + (6))/((2)) = g \\ (14)/(2) = g \\ g = 7

User Thomas F
by
6.2k points